The Legal Protection Policy for Partnerships in Socially Just, Digital-Based Land Transportation Businesses - Agatha Jumiati; Harun Harun; Absori Absori; Kelik Wardiono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The development of legal relations between drivers and online land transportation service application providers is becoming increasingly massive, especially when technological developments and digitalization make it easier to utilize digital-based land transportation services. This research aims to analyze and determine legal prescriptions or solutions to the problem of legal gaps in special regulations that discuss and serve as guidelines in implementing partnership legal relations between online transportation drivers and online land transportation service application providers in terms of the aspect of social justice. This research is normative legal research by prioritizing conceptual and statutory approaches. The research results confirm that the social justice aspect of the partnership legal relationship between drivers and online land transportation service application providers has not actually been fulfilled, which is due to the absence of special regulations regarding partnership relationships that can guarantee legal certainty and protection for online transportation service drivers. Legal protection policies for partnership legal relationships between drivers and online land transportation service application providers can be implemented by establishing regulations regarding special partnership relationships between drivers and online land transportation service application providers to fill the existing legal gaps.